Giant egg capsules and hatchlings in a deep-sea moon snail (Naticidae) from a Southwestern Atlantic Canyon - Penchaszadeh, Pablo Enrique (2016)
The globose moon snail Bulbus carcellesi Dell, 1990 (Naticidae), and its egg masses were collected from the Mar del Plata Submarine Canyon at depths of 201–2082 m) in August 2012 and May 2013. Embryos of this species undergo encapsulated development, and the egg capsules are the largest ever recorded for this family, 8.8–14.1 mm in diameter. The largest naticid egg capsule previously recorded was only 3 mm. Each egg capsule contains a single, 200-µm diameter egg and a considerable amount of white material (supplementary food), which allows the embryo to grow to an enormous size (up to 6.0 mm in shell diameter) before hatching as a crawling juvenile. The volume of this juvenile shell is 45 times the volume of previously reported naticid hatchlings. This great size and the number of whorls in the hatchling shell suggest a slow rate of development, akin to many other deep-sea invertebrates.